The Impact of Using Think Pair Share Technique on the Students’ Speaking Skill - Cut Misria; Asnawi Muslem; Yuliana Natsir (Universitas Syiah Kuala, 2020)
This study aims to find out whether the use of Think Pair Share technique can improve students’ speaking skill. This research was conducted at the second grade students of SMA Negeri 1 Simpang Ulim, Aceh Timur, Indonesia. The method of this study was quantitative research (experimental study) with one group pre-test and post test design. The sample of this research was one class at XI MIPA 1 which consists of 20 students. The researcher used an oral test about giving opinion (analytical exposition text) as an instrument in collecting the data. In analyzing the data, the researcher used statistical formula. The calculation result showed that the mean score of students pre-test was 33.75 and the mean score of post-test was 55. Furthermore, the t-score was 8.23 and t-table was 2.093. Thus, the t-score was higher than t-table. It means that the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. In this case, applying Think Pair Share technique in learning English Foreign Language had a positive impact for the students to improve speaking skill.